Desafios contemporâneos da Ciência da Informação: influenciadores digitais como objetos de investigação - Dantas, Melina Simardel (2018)
Constantly, new informational practices have been strengthened by virtual and collaborative information and communication technologies in contemporary times. In this context, the (informational and communicational) practices used by digital influencers consist of a new information action, which, according to this work, have been poorly explored in the scientific perspective of Information Science (IS). In this scenario, the general objective of this research was to bring the IS closer to the new actions of production and consumption of information on the web promoted by digital influencers, analyzing how studies of these new informational practices and informational individual would fit the scope of Information Science. Based on bibliographical research and literature review, studies were carried out both to contextualize and characterize IS, information as its object of study and contemporary users of information, as well as to understand the current informational individuals and current information and communication practices, to produce relations between Information Science and digital influencers. It was noticed that IS, in its evolution as a scientific area, has become a science capable of investigating a wide range of contents, not being restricted to the technical and theoretical aspects related to information, being also in the field research related to the aspects applied and social information uses and users. The objective was to understand, describe and contextualize the digital influence and digital influencers in IS, suggesting approximations of the topic in the range of the Working Groups (WGs) of the National Meeting of Research in Information Science (ENANCIB), indicating possible tendencies for studies about digital influencers in Information Science.